2000
DOI: 10.1038/sj.gene.6363719
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of new polymorphisms in the 5′UTR of the human interleukin-1 receptor type 1 (IL1R1) gene: linkage to type 1 diabetes and correlation to IL-1RI plasma level

Abstract: The human interleukin-1 type I receptor (IL-1RI) is the signal transducing receptor for IL-1, a principal proinflammatory cytokine, which is cytotoxic to pancreatic islet beta cells. The IL-1RI gene, IL1R1, maps to chromosome 2q12. We have previously examined part of the IL1R1 promoter region and in the present study we further characterized the promoter region demarcating exon 1B and 1C by sequencing and mutation scanning. New sequence was obtained 1762 bp upstream and 1609 bp downstream the known region. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Indeed, we, and others, have previously reported nucleotide sequence polymorphism in the promoter region spanning introns 1A-1C. [27][28][29][30][31] In the present report, we describe the identification and characterisation of a further eight novel polymorphisms in the IL1R1 promoter. Recently, a number of reports have indicated that polymorphic IL-1 haplotypes or extended haplotypes, as opposed to single locus polymorphisms, may provide better genetic markers of transcriptional activity and disease association, 32 in particular with the complex nature of the IL-1 agonist/antagonist relationship and the two IL-1 receptors.…”
Section: Introductionmentioning
confidence: 51%
“…Indeed, we, and others, have previously reported nucleotide sequence polymorphism in the promoter region spanning introns 1A-1C. [27][28][29][30][31] In the present report, we describe the identification and characterisation of a further eight novel polymorphisms in the IL1R1 promoter. Recently, a number of reports have indicated that polymorphic IL-1 haplotypes or extended haplotypes, as opposed to single locus polymorphisms, may provide better genetic markers of transcriptional activity and disease association, 32 in particular with the complex nature of the IL-1 agonist/antagonist relationship and the two IL-1 receptors.…”
Section: Introductionmentioning
confidence: 51%
“…142,143 A number of genes have been proposed and investigated as candidate genes for the IDDM7 region. These include genes of the interleukin-1 gene cluster (ie IL1R1, [144][145][146] IL1B, 130,147,148 and IL1RN 130,149 ) HOXD8, 150 GAD1, 151 GALNT3, 141 and NEUROD. [152][153][154] However, linkage or association has not been convincingly demonstrated for any of these candidate genes.…”
Section: Iddm2-the Insulin Gene (Ins) Regionmentioning
confidence: 99%
“…A SNP allele in the interleukine1-type 1 receptor (IL1R1) apparently leads to low plasma concentrations of IL-1-R1 and was reported to be associated with type 1A diabetes [129]. In Japanese patients, but not in Italian patients, an Arg140Trp mutation has been identified in the CD38 gene, which is a non-lineage pleiotropic cell surface receptor.…”
Section: Other Genes and Locimentioning
confidence: 99%